1987
DOI: 10.1203/00006450-198701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inspiratory Resistive Loading on Costal and Crural Diaphragm Electromyograms in Piglets

Abstract: ABSTRAff. We examined the effect of inspiratory resistive loaded breathing (IRL) on the electromyographic (EMG) activity of the costal and crural diaphragm in nine anesthetized spontaneously breathing piglets (age 10-23 days, weight 2.8-4.4 kg). Bipolar wire electrodes were inserted into the anterior paratendinous costal diaphragm and the midportion of the crural diaphragm. EMG activity was quantified in arbitrary units ( Experimental evidence from adult animal studies suggests that the costal and crural porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In support of this concept, we have recently reported that the inspiratory EMG activity of the diaphragm is differentially distributed between its costal and crural components during inspiratory resistive loaded breathing in piglets (8). Specifically, we observed a greater augmentation in crural EMG activity when compared to its costal counterpart during the period of loaded breathing.…”
supporting
confidence: 78%
“…In support of this concept, we have recently reported that the inspiratory EMG activity of the diaphragm is differentially distributed between its costal and crural components during inspiratory resistive loaded breathing in piglets (8). Specifically, we observed a greater augmentation in crural EMG activity when compared to its costal counterpart during the period of loaded breathing.…”
supporting
confidence: 78%
“…3 The crural diaphragm was selected for EMG recordings since it exhibits preferential augmentation during resistive loaded breathing. 6,7 The electrode placement was accomplished without laparotomy due to its potential adverse effects on diaphragmatic function. 8 A third electrode was placed subdermally at the base of the buttocks to provide an electrical ground.…”
Section: Methodsmentioning
confidence: 99%
“…Serial sections as a model in which to study diaphragmatic muscle function in were meincubated at alkaline pH (10.3) and at acid pH (4.5 and a developmental context (12)(13)(14)(15)(16)(17). The normal pattern of periph-4.3) prior to the myofibrillar ATPase assay (24).…”
Section: Methodsmentioning
confidence: 99%